Selective excision of 5-carboxylcytosine by a thymine DNA glycosylase mutant - Hashimoto, Hideharu (2013)
The mammalian thymine DNA glycosylase (TDG) excises the mismatched base, uracil, thymine, or 5-hydroxymethyluracil (5hmU), as well as removes 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC) when paired with a guanine. In the previously solved structure of TDG in complex with DNA containing 5caC, the side chain of asparagine 157 (N157) contacts the 5-carboxyl moiety of 5caC via a weak hydrogen bond. We examined the role of N157 in recognition of 5caC by mutagenesis. The asparagine-to-alanine (N157A) mutant has no detectable base excision activity for a G:T mismatch, and its excision activity is reduced for other substrates including G:5caC. Unexpectedly, the asparagine-to-aspartate (N157D) mutant has a comparable base excision rate for G:5caC substrate to that of wild type, but it only has residual activity for G:U and no detectable activity for other substrates. We further show that the N157D mutant has higher activity for 5caC at a lower pH (6.0), suggesting that increased protonation of the carboxylate of 5caC and the aspartate facilitates base excision. The N157D mutant remains highly specific for 5caC even in the presence of large excess of genomic DNA, a property that can potentially be used for mapping the very low amount of 5caC in genomes.